Demographic profile of subjects undergoing sphenoidotomy for sphenoid sinusitis, in a tertiary care centre of Punjab- analysis of 75 subjects - Munjal, Manish; Sethi, Suneet; Chowdhary, Anurag; Munjal, Shubham; Sood, Ananya; Thind, Amrita; Walia, Rishabh (International Journal Of Community Medicine And Public Health, 2020)
Background: The demographic profile of patients with Sphenoiditis undergoing surgical intervention, in the state of Punjab was studied. The emphasis was on the age, gender and clinical presentation in this prospective study. Methods: There were 75 patients of sphenoethmoidal recess pathology with sphenoditis, who were selected from the Rhinology clinics of Otorhinolaryngology and head Neck services of Dayanand Medical College and Hospital Ludhiana , in a period one and a half years (November 2002 to October 2004). All patients were taken up for Functional endoscopic sinus surgery of the sphenoid sinus surgery with sphenoidotomy. Results: The age range of subjects with sphenoiditis was between 12 years to 70 years. The mean age was 38.13 years. The maximum number of patients were in 19-30 years age group and the minimum in 31-40 years age group. Males outnumbered the females by a ratio of 1.7:1. The most common was posterior nasal drip (69.33% cases) behind the Eustachian tube and the least common complaint was diplopia (5.33% cases. Ocular involvement was observed in 32%. The right eye was more frequently involved (17.33%) as compared to the left (12%). Conclusions: Patients with Sphenoid sinusitis were seen in the broad age range from 19 to 30 years with a male predominance. Posterior nasal discharge behind the Eustachian tube, rather than the typical occipital ache was the primary complaint .Right sided eye involvement with ptosis and lateral rectus palsy were commonly noted.